The later Stuart Church, 1660-1714 - Tapsell, Grant (Politics, culture, and society in early modern Britain., 2017)
This book features nine essays written by leading scholars in the field to offer new insights into the place of the Church of England within the volatile Restoration era. Sections on ideas and people include essays covering the royal supremacy, the theology of the later Stuart Church and clerical and lay interests.